Pictures, Dreams, and the Reflexive Educational Reformer - Mark Campbell Williams (Networks: An Online Journal for Teacher Research, 2000)
What do pictures, dreams and reflection have to do with educational reform? In this paper I reflect heuristically on a five year study investigating a major teaching reform of a university business computing course. I conducted action research on a raft of teaching innovations designed to introduce communication, discourse, and reflection on broad social and organisational implications of computing rather than merely hardware and software techniques. The main theme was to see if discourse could ameliorate a dominant technicism in the teaching-learning process and curriculum. After three years, I realised that, in my own technicist drive to achieve "success" and significant research results, I had acted unethically by coercing students to give me certain research data and by not fully informing students or other lecturers and tutors about important aspects of the research. I thus discontinued the research and concentrated on a heuristic and reflective phenomenological self-study, including dreams and pictures, on the reasons for and the nature of my unethical practice.
Keywords: Open discourse; technicism; heuristic research; dreams; rich pictures; university teaching reform